Kajian Teoretis Perilaku Prososial, Agresi, dan Dinamika Kelompok dalam Perspektif Teori Identitas Sosial - Putri, Ratih Meyrani; S., Neviyarni (Lembaga Yasin AlSys, 2025)
This article presents a theoretical review of prosocial behavior, aggression, and group dynamics within the field of social psychology, based on the Social Identity Theory developed by Tajfel and Turner (1979). The purpose of this review is to understand how helping behavior, aggressive actions, and intergroup interactions can be explained through the processes of categorization, identification, and social comparison. The method employed is a literature review, examining social psychology theories and previous research findings related to social behavior in both academic settings and the broader community. The analysis reveals that prosocial behavior is generally driven by empathy and internalized social values, while aggressive behavior more often arises as a response to frustration or perceived threats to social identity. Group dynamics play a critical role in shaping self-identity, fostering a sense of belonging, and reinforcing social solidarity. The application of Social Identity Theory in this context offers deeper insights into the complex relationship between individuals and groups, highlighting the importance of fostering inclusive, collaborative, and identity-sensitive social environments.